Cepharanthine induces ROS stress in glioma and neuronal cells via modulation of VDAC permeability - Karolina Cierluk; Wojciech Szlasa; Joanna Rossowska; Mounir Tarek; Anna Szewczyk; Jolanta Saczko; Julita Kulbacka (Elsevier, 2020)
Cepharanthine (CEP) is a bisbenzylisoquinoline alkaloid. Molecular dynamics studies show that CEP interacts with Voltage-dependent anion channel (VDAC), inducing the voltage-independent channel narrowing. In the new conformation, transport between mitochondria and cytoplasm is altered, which leads to the dose-dependent cytotoxicity.The biological effects of the interaction were investigated on glioblastoma multiforme (SNB-19) and neuronal (PC-12 + NGF) cell lines. The cytotoxic potential of cepharanthine was determined by MTT assay and flow cytometry apoptosis/necrosis studies. T-type calcium channel and VDAC were labelled by the immunocytochemical method. Additionally, fluorescent labelling of reactive oxygen species and mitochondria was performed. Changes in the pore size of VDAC were calculated as well. Molecular dynamics simulations were carried out to examine the interactions of cepharanthine with VDAC.The obtained results prove that cepharanthine enhances the apoptosis in glioma and neuronal cells by the release of reactive oxygen species. Cepharanthine alters the mitochondria-to-cytoplasm transport and thus induces the cytotoxicity with no selectivity.